2021
DOI: 10.3390/jcm10010133
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Prognostic Implications of Cardiac Arrhythmias in Patients Hospitalized for COVID-19

Abstract: Background: Cardiac manifestation of COVID-19 has been reported during the COVID pandemic. The role of cardiac arrhythmias in COVID-19 is insufficiently understood. This study assesses the incidence of cardiac arrhythmias and their prognostic implications in hospitalized COVID-19-patients. Methods: A total of 166 patients from eight centers who were hospitalized for COVID-19 from 03/2020–06/2020 were included. Medical records were systematically analyzed for baseline characteristics, biomarkers, cardiac arrhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 26 publications
0
62
1
3
Order By: Relevance
“…Of the 783 studies identified from the literature search (216 on Pubmed and 567 on EMBASE), 31 studies were selected according to the inclusion and exclusion criteria and included in the analysis [ 3 , 10 , 11 , 12 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] ( Figure S1 in Supplementary Materials ), with a total of 187,716 COVID-19 patients. Baseline characteristics of the studies included are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 783 studies identified from the literature search (216 on Pubmed and 567 on EMBASE), 31 studies were selected according to the inclusion and exclusion criteria and included in the analysis [ 3 , 10 , 11 , 12 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] ( Figure S1 in Supplementary Materials ), with a total of 187,716 COVID-19 patients. Baseline characteristics of the studies included are reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were held in Europe [ 10 , 11 , 25 , 29 , 31 , 33 , 37 , 39 , 42 , 43 , 44 , 47 , 50 ], nine in North America [ 3 , 28 , 30 , 32 , 41 , 45 , 46 , 49 , 51 ], four in Asia [ 26 , 34 , 35 , 48 ], and five in other geographical locations, including one multinational study [ 12 , 27 , 36 , 38 , 40 ]. Twenty-five studies were observational retrospective [ 3 , 10 , 12 , 26 , 28 , 30 , 31 , 32 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], four were based on prospective observational analysis of single center cohorts [ 11 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations